Depenalization of Medical Personnel Practicing Without a Practice License After the Enactment of the 2023 Health Law - Manuaba, Ida Ayu Lidya Nareswari; Potabuga, Siska Dewi Indriani; Lamawatu, Nuril F. (Ius Poenale, 2025)
The background of this research is that a doctor, as a medical professional, plays a crucial role in the healing process of patients based on knowledge and competence. The issue of doctors practicing without a valid practice license (SIP) has often been heard before the enactment of Law Number 17 of 2023 concerning Health, where the regulation on criminal sanctions for doctors practicing without an SIP was found in Law Number 29 of 2004 concerning Medical Practice. However, after the enactment of Law Number 17 of 2023 concerning Health, the regulation on criminal sanctions has been removed, leaving only administrative sanctions in effect. This research aims to explore the concept of depenalization for medical personnel practicing without a valid practice license after the enactment of Law Number 17 of 2023 concerning Health. The type of research used in this study was normative research, employing both a statutory approach and a conceptual approach. The findings of the study indicate that if the actions of the doctor can be proven in a factual judgment (judex facti), the concept of depenalization with the imposition of criminal sanctions should be considered, while setting aside the principle of economic deterrence.